Investigation of Surface Hardness, Combustion Behavior and Electromagnetic Shielding Properties of Wood Composite Coated with Vermiculite-Doped Rigid Polyurethane - Kaya, Ali; Kırbaş, İbrahim; Çifci, Ahmet (Osman SAĞDIÇ, 2019)
In this study, vermiculite, which is used as a mineral material for thermal and insulation purposes, was added to rigid polyurethane material and used in the surface coating of two different wood composite materials. Vermiculite was added to the total polyurethane mass by 5% and 10%. In the study, medium density fiberboard (MDF) and plywood were used as wood composite materials. The combustion behavior of wood composite materials coated with rigid polyurethane was examined in accordance with TS EN ISO 11925-2 standard with single source flame test and mass loss and thermal permeability values according to DIN 4102 and TS en 13823 standard. In addition, surface hardness and electromagnetic shielding properties of the materials were determined. According to the experimental results, it was determined that vermiculite additive in wood composites whose surface is covered with polyurethane contributes positively to the combustion resistance of both materials. While surface hardness gives good results in plywood materials, it is determined that mass loss and thermal permeability values give better results in MDF materials. In the experiments, it has been observed that as the ratio of vermiculite at the measured frequencies increases, the electromagnetic shielding property also increases.

Bu çalışmada mineral madde olarak ısıl ve yalıtım amaçlı kullanıma sahip olan vermikülit, sert poliüretan malzemeye eklenerek iki ayrı ahşap kompozit malzemenin yüzey kaplamasında kullanılmıştır. Vermikülit toplam poliüretan kütlesine %5 ve %10 oranında eklenmiştir. Çalışmada ahşap kompozit malzeme olarak orta yoğunlukta lif levha (Medium Density Fiberboard – MDF) ve kontrplak (Plywood) kullanılmıştır. Sert poliüretan ile yüzeyleri kaplanan ahşap kompozit malzemelerin yanma davranışı TS EN ISO 11925-2 standardına göre tek kaynaklı alev testi ile kütle kaybı ve ısıl geçirgenlik değerleri DIN 4102 ve TS EN 13823 standardına göre incelenmiştir. Ayrıca malzemelerin yüzey sertlikleri ve elektromanyatik ekranlama özellikleri belirlenmiştir. Deneysel sonuçlara bakıldığında yüzeyi poliüretan ile kaplanmış ahşap kompozitlerde vermikülit katkısının her iki malzemenin yanma direncine olumlu katkı yaptığı belirlenmiştir. Yüzey sertliği kontraplak malzemlerde iyi sonuçlar verirken kütle kaybı ve ısıl geçirgenlik değerinin MDF malzemelerde daha iyi sonuçlar verdiği belirlenmiştir. Deneylerde ölçüm yapılan frekanslarda ağırlıkça katkılama oranı arttıkça elektromanyetik ekranlama özelliğinin artığı görülmüştür.
Vermikülit Katkılı Sert Poliüretan ile Kaplanmış Ahşap Kompozitlerin Yüzey Sertliğinin, Yanma Davranışlarının ve Elektromanyetik Ekranlama Özelliklerinin İncelenmesi
Keywords: Engineering; Mühendislik